Student’s Communication Skills Based on Involvement in the Organizations - Mutiara Ulva Salsabilla; Daharnis Daharnis (Universitas Negeri Padang, 2022)
Communication is the process of exchanging messages, where these messages can be in the form of facts, ideas, feelings, data or information from one person to another. Communication failure can be a problem for human life, this failure is caused by various factors, both from the communicating subject and the object being communicated. Problems that occur can be caused by communicators and communicants who do not understand each other's flow of communication, so that the signal is not given and a good communication system is not formed. This study aims to: (1) describe the communication skills of students who are involved in organizations, (2) describe the communication skills of students who are not involved in organizations, and (3) examine the differences in the communication skills of students who are involved in organizations and not involved in organizations.This research uses quantitative methods with comparative descriptive research. The population used in this study were 586 students of class XI and XII of SMAN 13 Padang who were registered in the 2022/2023 academic year with a research sample of 76 students using the purposive sampling technique. Collecting data in this study using a questionnaire of students' communication skills with a Likert scale model. The data processing technique used descriptive statistical analysis and the Mann-Whitney test technique.The results showed that: (1) the communication skills of students involved in the organization were in the good category (2) the communication skills of students who were not involved in the organization were on average in the fairly good category, and (3) there were significant differences in students' communication skills. based on involvement in the organization; communication skills of students who are involved in the organization are better than the communication skills of students who are not involved in the organization.